Defining the Properties of pH -sensitive Polymeric Micellar Ocular Delivery System of Miconazole Nitrate for the Management of Fungal Endophthalmitis - Agrawal, Vaishali; Kumar, Manish; Pathak, Kamla (Pharmaceutical Nanotechnology, 2014)
The investigation was aimed at developing polymeric micellar ocular delivery system of miconazole nitrate for efficient management of fungal endophthalmitis. Drug loaded micelles of tri-block copolymers Pf 127 and Pf 68 were prepared by solvent evaporation method. The polymeric micelles (F1 to F12) were assessed for entrapment efficiency, micelle size and in vitro permeation. Formulation F2 with the lowest micelle size of 80.5 nm, least polydispersity value of 0.105, highest entrapment efficiency of 89.25±2.00% and a cumulative drug permeation of 92.28±1.95% in 8h, was selected to develop pH-sensitive micelles loaded carbopol in situ gel. Of the five gel formulations screened (G1-G5), G5 was selected on the basis of optimum physicochemical characteristics. A comparative ex vivo transcorneal permeation study between G5, F2 and pure drug, using intact goat cornea analyzed the ability of formulations to achieve target concentration. While F2 achieved the target concentration (96.59±0.65%) in 6 hrs, G5 showed sustained release and achieved target concentration (96.9±1.27%) in 8 hrs in contrast to 26.96±0.75% permeation achieved by pure drug solution in 8 hrs. The results indicated controlled permeation of drug across the cornea 8 hrs via optimized in situ formulation G5. Zero score in HET CAM test indicated non-irritant property of G5 and histological studies revealed no visual signs of corneal tissue damage suggesting ocular safety of the optimized in situ gel.
Keywords: polymeric micelles